Kinematic and Temporospatial Changes in Children with Cerebral Palsy during the Initial Stages of Gait Development. (2nd January 2022) - Dimakopoulos, Rigas; Syrogiannopoulos, George; Grivea, Ioanna; Dailiana, Zoe; Youroukos, Sotirios; Spinou, Arietta
ABSTRACT: Purpose: To identify changes in the gait kinematics and temporospatial parameters of children with bilateral Cerebral Palsy (CP) at 8 months after the onset of independent walking and identify differences to Typical Development (TD) children at the onset of independent walking and at 8 months follow up. Method: Sixteen children with bilateral CP, GMFCS levels I and II, and 15 TD children were recruited. Gait kinematics and temporospatial parameters were recorded using a 3-D gait analysis system; the sagittal plane of the lower limb joints was analyzed. Baseline measurements were recorded at the individual's onset of independent walking and follow up was after 8 months. Results: Compared to baseline, children with bilateral CP demonstrated increased (mean difference ± SE) plantar flexion (11.79 ± 2.96), single support (0.04 ± 0.01), step length (0.2 ± 0.05) and stride length (0.4 ± 0.09), at follow up; all p < .05. Compared to TD children, they also had lower gait speed (0.16 ± 0.05), higher single support (0.02 ± 0.01) and lower maximum knee extension (9.14 ± 4.49) during the swing phase, at baseline and follow up (0.1 ± 0.04, 0.05 ± 0.01, 23.04 ± 4.17, respectively); all p < .05. Conclusion: There are changes in the sagittal plane kinematics and temporospatial parameters of the gait during the first 8 months of independent walking. These indicate gait maturation changes and highlight the impact of walking experience on the gait characteristics of children with bilateral CP.